Changing perceptions: L&T acquisition of Mindtree - Kaul, Asha (Henry Stewart Talks, 2022)
This case study examines the use of media narratives for changing corporate reputation, using the example of Larsen and Toubro (L&T)’s merger with Mindtree, which was a contentious process.